Perception of Toxic Habits in Adolescents in Educational Units of the Ambato Canton - Carlos Alejandro Troya Altamirano; Eduardo Leonel Alvarado Pico; Andrea Gabriela Suárez López (Medisur)
Foundation: toxic habits in adolescents can have negative consequences for their well-being, which is why guidance through health education actions is necessary. Objective: to describe the perception of toxic habits in adolescents in educational units of the Ambato canton. Methods: a descriptive cross-sectional study was carried out with adolescents from 5 educational units in the Ambato canton. The sample was selected through simple random sampling and was made up of 93 adolescents of both sexes. The variables were analyzed: sex, consumption of toxic substances, frequency of consumption, knowledge about health effects derived from toxic habits, experience of the harmful effects derived from toxic habits, need for health care, need to adopt lifestyle habits. healthy and the need for joint training between education and health professionals. The information was collected through the survey technique. The data were analyzed using descriptive statistics (absolute and relative percentage frequency) using SPSS software. Results: 73.11 % admitted to having consumed some toxic substance. Smoking and alcoholism are the most frequent toxic habits (36.56 and 25.81 % respectively). Sporadic consumption was the most frequent (40.86 %). 96.8 % admitted knowing how toxic habits affect them. 93.5 % reported having experienced harmful effects. 94.6 % of those studied reported that health care was not necessary. 84 % recognized the need to adopt healthy lifestyle habits. Conclusions: the health education actions undertaken in the educational units have not been effective. There is a need to continue providing knowledge and delve into the effects and risks of alcohol, tobacco and drug consumption and the need to adopt healthy lifestyle habits. It is a necessity that educational units can create alliances and cooperation projects with the health institutions of the communities where they are located.